Management of the penile squamous cell carcinoma patient after node positive radical inguinal lymph node dissection: current evidence and future prospects. Issue 2 (March 2020) - de Vries, Hielke M.; Ottenhof, Sarah R.; van der Heijden, Michiel S.; Pos, Floris J.; Horenblas, Simon; Brouwer, Oscar R.
Abstract : Purpose of review: The level of evidence for current (adjuvant) treatment strategies after node positive inguinal lymphadenectomy is relatively low because of a paucity of prospective studies and controversy exist between the two major guidelines. The present review aims to provide a review of current literature on the available treatment options of patients after a tumor positive inguinal lymph node dissection. Recent findings: Patients without inguinal extranodal extension or less than two tumor positive inguinal nodes are at low risk of ipsilateral pelvic nodal disease. Patients with pN1 disease are unlikely to benefit from adjuvant treatment, whereas patients with pN2 disease might benefit from adjuvant radiotherapy. For patients with high risk of pelvic nodal disease, prophylactic pelvic lymph node dissection (PLND) is advised by current guidelines. The InPACT study investigates whether adjuvant chemoradiotherapy could be used instead of prophylactic PLND. Subgroup analyses of retrospective cohorts suggest that patients with pN3 disease based on tumor positive pelvic nodes may benefit from adjuvant radiotherapy or chemotherapy. Given the weak level of evidence and substantial toxicity associated with current regimens, adjuvant chemotherapy cannot be generally recommended. Summary: Despite current treatment strategies, patients with pN2–pN3 disease still have a poor prognosis. Prospective international multicenter studies are necessary to identify the best treatment options for patients with advanced node positive penile squamous cell carcinoma.